2008
DOI: 10.1016/j.hrthm.2008.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Cellular basis for arrhythmogenesis in an experimental model of the SQT1 form of the short QT syndrome

Abstract: Background-Short QT syndrome (SQT) is a primary electrical disease associated with a high risk of sudden cardiac death. A gain-of-function in I Kr , due to a mutation in KCNH2, underlies SQT1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 24 publications
4
65
0
Order By: Relevance
“…Hansen et al (2008) also reported that in vivo treatment of guinea pigs with NS3623 produced a reversal of E4031-induced prolongation of the QT interval. In the absence of pharmacologic blockade of hERG1, Patel and Antzelevitch (2008) reported that the hERG1 activator PD118057 abbreviated the QT interval but increased transmural dispersion of repolarization. This leads to polymorphic ventricular tachycardia induction in a canine wedge preparation (Patel and Antzelevitch, 2008).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation
“…Hansen et al (2008) also reported that in vivo treatment of guinea pigs with NS3623 produced a reversal of E4031-induced prolongation of the QT interval. In the absence of pharmacologic blockade of hERG1, Patel and Antzelevitch (2008) reported that the hERG1 activator PD118057 abbreviated the QT interval but increased transmural dispersion of repolarization. This leads to polymorphic ventricular tachycardia induction in a canine wedge preparation (Patel and Antzelevitch, 2008).…”
Section: Downloaded Frommentioning
confidence: 99%
“…In the absence of pharmacologic blockade of hERG1, Patel and Antzelevitch (2008) reported that the hERG1 activator PD118057 abbreviated the QT interval but increased transmural dispersion of repolarization. This leads to polymorphic ventricular tachycardia induction in a canine wedge preparation (Patel and Antzelevitch, 2008). Thus, it is still uncertain whether hERG1 activators will be antiarrhythmic or prodysrhythmic.…”
Section: Downloaded Frommentioning
confidence: 99%
“…Augmented TDR as the basis for arrhythmogenesis in SQTS has been demonstrated in experimental models in which repolarization is abbreviated using the I Kr agonist, PD-118057, 28 thus mimicking the cellular conditions created by the genetic defect associated with SQT1. Dispersion of repolarization and refractoriness serve as substrates for reentry by promoting unidirectional block.…”
Section: Mechanism Of Arrhythmia In Sqtsmentioning
confidence: 99%
“…Insight into the effect of [73]. Subsequent use of an I Kr -activating compound (PD-118057) in experiments with the ventricular wedge preparation has shown QT interval shortening, increased TDR and ERP abbreviation and susceptibility to evoked arrhythmia [74].…”
Section: Mechanisms Of Arrhythmogenesismentioning
confidence: 99%